Diffuse large B-cells lymphoma clinical features in patients with hepatitis B and C infection - G. I. Storozhakov; V. A. Khailenko; V. M. Scherstnev (Онкогематология, 2022)
Examination results of 59 patients with diffuse large B-cells lymphoma (DBLCL) and hepatitis C and B infection are presented. Control group was constituted by 59 patients with DLBCL without virus markers. The obtained results suggest possible etiopathogenetic role of hepatitis C virus in DLBCL development that clinically displayed more frequent spleen lesion and overall survival improvement in this subgroup of patients.